2015
DOI: 10.1016/j.ecolmodel.2015.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Structure-dynamic relationship of plant–insect networks along a primary succession gradient on a glacier foreland

Abstract: There is a growing interest in understanding the structure-dynamic relationship of ecological networks. Ecological network changes along primary successions are poorly known: to address such topic, gradient of primary succession on glacier forelands is an ideal model, as sites of different age since deglaciation stand for different ecosystem developmental stages. We aimed to investigate the assembly processes of plant-insect networks and to elucidate its functional implications for ecosystem stability along th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…Further, aggregating species into larger functional groups would be a probably interesting research direction (aggregation based on either traits or network topology; Garibaldi et al, 2015), while some patterns at the network level can be better understood in the light of metrics analysed at the species level (Soares et al, 2017;Kovács-Hostyánszki et al, in prep). It should be also important to merge plant-pollinator interactions with others in unified models (see Losapio et al, 2015). As of particular interest, both from a network dynamics point of view and also biologically, we have to better understand dwarf components: why are these species not connected to the giant component and how could they be connected (though which other species)?…”
Section: Discussionmentioning
confidence: 99%
“…Further, aggregating species into larger functional groups would be a probably interesting research direction (aggregation based on either traits or network topology; Garibaldi et al, 2015), while some patterns at the network level can be better understood in the light of metrics analysed at the species level (Soares et al, 2017;Kovács-Hostyánszki et al, in prep). It should be also important to merge plant-pollinator interactions with others in unified models (see Losapio et al, 2015). As of particular interest, both from a network dynamics point of view and also biologically, we have to better understand dwarf components: why are these species not connected to the giant component and how could they be connected (though which other species)?…”
Section: Discussionmentioning
confidence: 99%
“…Nestedness of plant facilitation networks has been proposed to be also responsible for driving ecological succession as networks become more nested with increasing successional age (Losapio et al 2018a). This suggests that the stability of ecological networks against species loss increases throughout ecological successions, as also evidenced by plant-insect network dynamics (Losapio et al 2015). Results from tropical forests (Marcilio-Silva et al 2015) also highlight the importance of species turnover over the influence of some species traits related to dispersal and canopy size.…”
Section: Functional Traits Spatio-temporal Dynamics and Conservationmentioning
confidence: 99%
“…Studies of macroorganisms generally find that interaction networks increase in complexity across succession. In pollination biology (Albrecht et al, 2010;Losapio et al, 2015) and work on animal food webs (Wardle et al, 1995;Neutel et al, 2007), network complexity (typically measured as the number of connections per species) increases due to the increase in quantity and diversity of resources over succession. Experiments have also shown that substrate limitation can constrain the complexity of animal food webs (Chen and Wise, 1999).…”
Section: Introductionmentioning
confidence: 99%